2013
DOI: 10.3111/13696998.2013.839946
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of utility weights in wet age-related macular degeneration

Abstract: Several instruments have been used to elicit utilities from patients with wAMD. Because TTO methods were more sensitive to VA changes than standard gamble and HUI3 estimates were most highly correlated with VA changes, TTO and HUI3 may be suitable methods for economic evaluations in these patients. The EQ-5D and SF-6D were poor indicators of the impact of VA on HRQL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…Another disparity that might count is that the EQ-5D score presents societal values of health states whilst the TTO reflects patients’ evaluations. Our findings are in line with and confirm the conclusions of previous systematic reviews on utility measurement in wet AMD [ 19 , 20 ]. Pearson et al found that the TTO measurement is a better indicator of the impact of visual acuity on HRQOL than the EQ-5D.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another disparity that might count is that the EQ-5D score presents societal values of health states whilst the TTO reflects patients’ evaluations. Our findings are in line with and confirm the conclusions of previous systematic reviews on utility measurement in wet AMD [ 19 , 20 ]. Pearson et al found that the TTO measurement is a better indicator of the impact of visual acuity on HRQOL than the EQ-5D.…”
Section: Discussionsupporting
confidence: 93%
“…Utilities are used to calculate the quality-adjusted life year (QALY) gains of different treatment strategies in cost-effectiveness analyses. Health state utility values in AMD were analysed in two recent systematic literature reviews and the time trade-off (TTO) method was found to be a suitable health state valuation technique in AMD [ 19 , 20 ]. The TTO consists of a hypothetical trade-off in which subjects are asked to indicate the number of life-years they would be willing to sacrify to avoid a well-defined poorer health state [ 21 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, several studies have demonstrated a link between ocular surface disease related to glaucoma therapy and reduced QoL in glaucoma patients . Glaucoma and AMD each impact utility values; it is plausible that patients with both conditions have poorer preference‐based status than those with glaucoma alone.…”
Section: Discussionmentioning
confidence: 99%
“…Both glaucoma and AMD can cause significant limitations on patients' daily activities, profoundly affecting their quality of life (QoL). However, the additive impact of AMD on vision‐related activity limitation or preference‐based status in patients with glaucoma has not previously been quantified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation